Strategi Meningkatkan Adopsi Inovasi Program Kartu Tani Di Kabupaten Banyumas, Jawa Tengah, Indonesia - Minarsih, Siti; Dharmawan, Budi; Eka Wijayanti, Irene Kartika (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
One of the most important production factors in increasing production and productivity of agricultural commodities is fertilizer. Moment this still many farmers who have not understand about the card program farmer as tool in distribution fertilizer subsidized , so required strategy for Upgrade adoption card program innovation farmer . The research aims to analyze internal and external factors as well as strategies to increase the adoption of innovations in the use of farmer cards in the district Banyumas . The research method used is a qualitative method. The analysis carried out is IFAS and EFAS matrix analysis, and SWOT analysis. The results showed that the internal and external factors of the farmer card program were in quadrant II, meaning that the alternative strategies used were building and growing strategies. This means increasing market share in the same market with more intensive marketing efforts, namely by assisting in more intensive distribution of subsidized fertilizers and product development by making economical packaging of subsidized fertilizers so that they are more attractive to the market. The results of the SWOT analysis include optimizing the role of institutions to provide clear and continuous information about innovations in the farmer card program, mentoring and counseling to improve farmers' knowledge and skills in implementing the farmer card program, developing product fertilizer subsidized for segment medium to lower that is with make packaging economical on fertilizer subsidized .